Reinforced chlorination purification method for high-purity quartz sand
By introducing gas reducing agents during the chlorination and roasting of quartz sand, the chemical bond fracture between impurities and oxygen is promoted, and the problem of difficult to deeply remove crystal structure impurities in conventional chlorination is solved, efficient and deep removal of impurities is achieved, and the purity of quartz sand is improved.
Patent Information
- Application Number
- CN202510621813.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-06-10
- Estimated Expiration
- 2045-05-15
AI Technical Summary
In the existing high-purity quartz sand production process, conventional chlorination roasting methods are difficult to achieve deep removal of crystal structure impurities (such as boron, aluminum, titanium, calcium and other impurities) in quartz sand.
By introducing a gas reducing agent during the chlorination and roasting process, it promotes the breakage of chemical bonds between impurities and oxygen, and then combines with the gas chlorination agent to form chloride and volatilize it.
It significantly improves the degree of dissociation and removal effect of difficult-to-remove impurity elements in the quartz lattice, achieves efficient depth removal of impurity elements, and improves the purity of quartz sand.
Smart Images

Figure CN120117613A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for purifying quartz sand, in particular to a method for enhanced chlorination purification of high-purity quartz sand, and belongs to the processing technical field of high-purity and high-end inorganic non-metallic materials. Background Art
[0002] High-purity quartz, as an indispensable basic material, plays a crucial role in multiple high-tech and emerging industries such as the semiconductor industry, fiber optic communication technology, photovoltaic energy field, and electric light source. It not only provides key material support for these fields but also is the core driving force for the rapid development of emerging industries such as the new generation of information industry, new energy technology, high-end equipment manufacturing, and new material research and development. Especially high-purity quartz sand of grade 4N8 and above, due to its almost stringent requirements for purity, has become the leader among high-end high-purity quartz products and is widely used in occasions with extremely high requirements for material purity. However, the production of high-purity quartz sand not only faces the challenge of scarce resources but also has a series of technical problems, making its production threshold relatively high.
[0003] Due to the congenital deficiencies in high-purity quartz mineral resources and the relatively lagging purification technology, it is currently difficult to produce high-purity quartz sand of grade 4N8 and above. The impurities contained in quartz minerals can be carefully classified into three categories according to their size, occurrence state, and physical and chemical properties: gangue mineral impurities, inclusion impurities, and crystal structure impurities. Gangue mineral impurities, such as mica and feldspar, often exist in the form of attached states on the surface of quartz sand particles or fill the tiny voids between the particles. Through a series of ore dressing technical means, especially the monomer dissociation process, these impurities can be effectively separated and removed from quartz minerals, thereby improving the purity of quartz. Inclusion impurities are the external substances or medium components during diagenesis and mineralization processes that are retained inside the crystal due to interface capture during the growth of mineral crystals. There is no direct chemical bonding relationship between them and the host quartz mineral. For the removal of such impurities, the roasting method is an effective means. Through high-temperature treatment, the inside of the inclusion will expand due to the increase in temperature. When the internal pressure reaches a certain level, the inclusion will undergo thermal explosion, thus achieving separation from the host quartz crystal. However, factors such as the composition, size, position, and shape of the inclusion in the quartz particle will have a significant impact on its explosion behavior at high temperatures. Specifically, some extremely small inclusions may remain intact even at extremely high temperatures because the internal pressure is difficult to accumulate to a level sufficient to trigger an explosion; inclusions located on the surface of quartz particles are more likely to explode at the same temperature compared to internal inclusions due to the lower external pressure; in addition, due to the structural asymmetry of irregularly shaped inclusions, they require a lower internal pressure during the explosion process compared to regularly shaped inclusions and are therefore more likely to achieve separation from the quartz crystal. Crystal structure impurities refer to elements that can replace silicon (Si) atoms in the silicon-oxygen tetrahedron, such as boron (B), aluminum (Al), titanium (Ti), etc. These substitution elements will form new tetrahedral structural units. Since this substitution is usually non-equivalent, that is, the differences in charge, radius, etc. between the substitution element and the silicon atom will lead to an unbalanced state of charge distribution inside the crystal lattice. To maintain the balance of lattice charge, some ions such as lithium (Li), sodium (Na), potassium (K), etc. will exist in the channel positions of the tetrahedral intervals to play a role in charge compensation. These crystal structure impurities are tightly bound by the silicon-oxygen tetrahedron structure, so it is difficult to achieve deep removal through conventional physical ore dressing methods such as magnetic separation and flotation, as well as chemical treatment methods such as acid leaching. Although the chlorination roasting technology has good effects on removing some elements such as potassium and sodium, its effects on removing impurity elements such as boron, aluminum, titanium, and calcium are not ideal. These impurity elements often show high stability during the chlorination process and are difficult to be effectively separated from quartz sand.
[0004] Given the complexity and difficulty of removing crystal structure impurities in quartz sand, it is particularly important to develop efficient and targeted deep removal technologies. This not only requires in-depth research on the occurrence states, migration laws, and interaction mechanisms with silicon-oxygen tetrahedrons of these impurity elements in quartz sand, but also the exploration of new treatment methods and technologies to achieve the efficient, low-energy-consuming, and environmentally friendly removal of impurity elements, so as to meet the strict purity requirements of high-end quartz materials. Summary of the Invention
[0005] Aiming at the fact that the conventional chlorination roasting method in the production process of existing high-purity quartz sand is difficult to achieve deep removal of crystal structure impurities (such as impurity elements like boron, aluminum, titanium, calcium, etc.) in quartz sand, the purpose of the present invention is to provide a method for enhanced chlorination purification of high-purity quartz sand. Based on the occurrence forms and chemical bond characteristics of impurity elements such as B, Al, Ti, Ca, etc. in quartz sand crystals during the chlorination purification process of quartz sand, the chemical bond breaking and recombination mechanism of the chlorination reaction of difficult-to-remove impurities is analyzed. A large number of experimental studies have shown that the chemical bonds formed by these difficult-to-remove impurity elements with oxygen in the quartz sand lattice are stable, and the chemical bond breaking is slow during the conventional chlorination roasting process. Therefore, it is difficult to deeply remove these impurity elements doped in the lattice. The present invention innovatively proposes to introduce a reducing medium to promote the breaking of the chemical bonds between the difficult-to-remove impurity elements and oxygen, and then strengthen the formation of chlorides of impurity elements for efficient volatilization and removal. This method specifically realizes the synchronous dissociation and chlorination of difficult-to-remove impurity elements, efficiently strengthens their removal, and only needs to introduce a gas reducing agent in the existing chlorination process, with advantages such as simple process, strong operability, strong raw material applicability, and high removal efficiency.
[0006] To achieve the above technical purpose, the present invention provides a method for enhanced chlorination purification of high-purity quartz sand. The method is to place the quartz sand raw material containing crystal structure impurities in a roasting furnace, and simultaneously introduce a gas chlorinating agent and a gas reducing agent into the roasting furnace for roasting to obtain purified quartz sand; the dosage of the gas chlorinating agent is 0.9 - 1.3 times the total molar amount of impurity elements in the quartz sand; the dosage of the gas reducing agent is 0.3 - 1.2 times the total molar amount of impurity elements in the quartz sand; the roasting conditions are: temperature is 900 - 1200 °C, and time is 5 - 30 min.
[0007] The quartz sand raw material containing crystal structure impurities involved in the present invention is preferably preliminarily purified quartz sand, such as quartz sand above 4N grade, which almost does not contain associated ore impurities and mainly retains trace crystal structure impurities.
[0008] The present invention aims at the occurrence form and chemical bond characteristics of crystal structure impurity elements in quartz sand. For example, impurity elements such as B, Al, Ti, and Ca have a strong oxygen-binding ability and stable chemical bond properties, which is the key reason why it is difficult to deeply remove impurity elements such as B, Al, Ti, and Ca in the quartz lattice by conventional chlorination roasting. The present invention ingeniously introduces a reducing medium synchronously during the chlorination roasting process. By utilizing the characteristic that the reducing medium at high temperature can promote the breaking of the chemical bond between the impurity elements and oxygen, it promotes the combination of the impurity elements with the chlorinating agent and then volatilizes and removes them. This method significantly improves the dissociation degree and removal effect of the difficult-to-remove impurity elements in the quartz lattice, realizing the deep and efficient removal of the impurity elements.
[0009] As a preferred embodiment, the gaseous chlorinating agent includes at least one of hydrogen chloride and chlorine. The chlorinating agents commonly used in the prior art are divided into gaseous chlorinating agents and solid chlorinating agents. Solid chlorinating agents, such as potassium chloride (KCl), calcium chloride (CaCl 2 ), etc., will decompose and release chlorine (Cl 2 ), etc. at high temperature and then participate in the subsequent chlorination reaction. However, these solid chlorinating agents may leave elements such as potassium and calcium in the reaction system during the high-temperature decomposition process, resulting in an increase in the content of elements such as potassium and calcium in the quartz sand, thereby affecting the purity and performance of the product. In contrast, gaseous chlorinating agents have significant advantages. They can not only effectively avoid the element residue problem caused by solid chlorinating agents, but also, due to their small molecular size and fast diffusion speed, can quickly react with the impurity elements in the quartz sand, thus improving the reaction efficiency and product quality of chlorination purification. Therefore, the present invention preferably uses conventional gaseous chlorinating agents such as hydrogen chloride and chlorine.
[0010] As a preferred embodiment, the gaseous reducing agent includes at least one of H 2 , CO, CH 4 . Gaseous reducing agents such as hydrogen (H 2 ), methane (CH 4 ), carbon monoxide (CO), etc. These gaseous reducing agents do not contain ash and have almost no residue under high-temperature reduction conditions, making them a better choice. In addition, the selection of gaseous reducing agents also needs to consider their molecular characteristics and chemical properties. If the medium has a large molecular weight or a high carbon element content in the molecule, their diffusion ability in the gaps between quartz sand particles will be limited, which will affect their reduction effect. Especially when the carbon element content is relatively high, carbon deposition may occur during the roasting process, resulting in carbon particles adhering to the surface of the quartz sand, which will not only reduce the purity of the product but also may have an adverse impact on its optical properties. Therefore, among the gaseous reducing media, hydrogen (H 2 ), carbon monoxide (CO), methane (CH 4Because of its moderate molecular weight, relatively low carbon element content, and easy diffusion and reaction, it becomes a preferred reducing medium and can be used alone or in combination to achieve the best effect.
[0011] The dosage of the gaseous chlorinating agent in the present invention is 0.9 - 1.3 times the total molar amount of impurity elements in quartz sand. The usage amount of the gaseous chlorinating agent directly determines the degree of removal of impurity elements. To ensure that the impurity elements in quartz sand can be effectively removed, the usage amount of the gaseous chlorinating agent must reach at least a critical value, which refers to the theoretical molar amount required to completely convert all impurity elements in quartz sand into corresponding metal chlorides. On this basis, moderately increasing the dosage of the chlorinating agent can produce positive effects. It can accelerate the process of the chlorination reaction, enabling impurity elements to be converted into metal chlorides faster, thereby improving the chlorination removal efficiency of impurities. However, it should be noted that when the dosage of the chlorinating agent is too high, although the removal efficiency may be further improved, the production cost will also increase accordingly, resulting in waste of resources. Therefore, in actual operation, a balance needs to be found. The preferred dosage of the chlorinating agent is usually set at 0.9 - 1.3 times the total molar amount of impurity metals in quartz sand, which can not only ensure effective removal efficiency but also control the production cost.
[0012] The dosage of the gaseous reducing agent in the present invention is 0.3 - 1.2 times the total molar amount of impurity elements in quartz sand. The dosage of the gaseous reducing medium is a key factor affecting the degree of breakage of the chemical bond between impurity elements and oxygen. If the dosage of the reducing medium is insufficient, the number of chemical bonds between impurity elements and oxygen that can be broken will be limited, resulting in poor reduction effect and ineffective removal of impurity elements. To increase the degree of breakage of the chemical bond, it is necessary to increase the dosage of the reducing medium. However, this also brings new problems. Excessive gaseous reducing medium may trigger other unnecessary chemical reactions. Therefore, when determining the dosage of the reducing medium, it is necessary to comprehensively consider the types and contents of impurity elements in quartz sand. Generally speaking, the preferred dosage of the reducing medium is 0.3 - 1.2 times the total molar amount of impurity elements in quartz sand, and this range can not only ensure effective reduction effect but also ensure the quality of quartz.
[0013] The roasting conditions of the present invention are as follows: the temperature is 900 - 1200 °C, and the time is 5 - 30 min. The roasting temperature is the core factor affecting the reaction behavior of impurity elements with gaseous chlorinating agents and gaseous reducing agents. As the roasting temperature increases, the reaction between impurity elements and gaseous chlorinating agents and gaseous reducing agents is accelerated, thus significantly improving the efficiency of impurity removal. However, the higher the temperature, the higher the temperature that the heating elements and lining materials of the furnace body need to withstand, which poses more stringent requirements for their heat resistance. At the same time, the energy consumption of the entire process also increases accordingly. And when the temperature is too high, solid-phase sintering is likely to occur between quartz sand particles, which will not only damage the particle size distribution of the product but also have an adverse impact on its overall quality. On the contrary, if the temperature is set too low, the reaction rate will be significantly slowed down, resulting in low production efficiency. Specifically, if the reaction time is too short, the reaction may not proceed completely, or the generated impurity chlorides cannot diffuse and be removed sufficiently from the interior of quartz sand particles; while if the reaction time is too long, the overall production efficiency will be affected.
[0014] As a preferred solution, the roasting furnace is a static roasting furnace or a dynamic roasting furnace. As a more preferred solution, when the roasting furnace is a dynamic roasting furnace, the horizontal inclination angle of the roasting furnace during the roasting process is 5 - 25°, and the rotation speed is 3 - 30 r / min. Compared with the crystalline roasting furnace, the present invention preferably adopts a dynamic roasting furnace, which can better promote the gas-solid reaction between quartz sand and gaseous chlorinating agents and gaseous reducing agents, and has a better effect on the deep removal of impurities in quartz sand. During the dynamic roasting of quartz sand, the inclination angle and rotation speed of the roasting furnace act together on the flow state of quartz sand, thereby affecting its movement trajectory and residence time in the furnace chamber. Specifically, the inclination angle and rotation speed of the dynamic roasting furnace are two key factors determining the flow rate of quartz sand. When the inclination angle is too large and the rotation speed is too fast, the residence time of quartz sand in the roasting furnace will be greatly shortened, which may lead to insufficient roasting and incomplete impurity removal. On the contrary, if the inclination angle is small and the rotation speed is slow, although it can ensure that quartz sand has sufficient roasting time in the furnace, thereby improving the impurity removal effect, it will also lead to a reduction in operation efficiency and is only applicable to processing raw materials with a high impurity content. Therefore, in actual operation, the optimal combination of the inclination angle and rotation speed of the roasting furnace needs to be found. Through practical verification, the preferred range of the inclination angle of the roasting furnace is 5 - 25°, and the rotation speed is 3 - 30 r / min, which can not only ensure a good impurity removal effect but also maintain a high production efficiency. The dynamic roasting furnace is, for example, a rotary kiln.
[0015] As a preferred solution, the SiO 2 content of the quartz sand raw material containing crystal structure impurities is ≥ 99.99%, and the SiO 2 content of the product quartz sand after chlorination is ≥ 99.995%.
[0016] Beneficial technical effects brought by the technical solution of the present invention compared with the prior art:
[0017] 1) The quartz sand purification method provided by the present invention is mainly based on the chemical bond characteristics and reaction mechanism of impurity elements in quartz sand. Through the synergistic effect of a chlorinating agent and a reducing agent, the breaking of chemical bonds of impurity elements and the formation of chlorides are efficiently regulated, realizing the efficient and deep removal of impurity elements. Compared with the traditional chlorination roasting process, the technology of the present invention not only significantly improves the removal efficiency of impurity elements, but also achieves a deeper purification effect in terms of the removal degree, providing a more high-quality production method of high-purity quartz sand for high-tech fields such as semiconductors and photovoltaics.
[0018] 2) The quartz sand purification method provided by the present invention shows extremely high flexibility and operability in application, and has a high degree of raw material applicability. It can be used for the deep purification of high-quality quartz resources or the quality upgrading of quartz resources of different grades, and can well adapt to different production requirements, providing more choices and possibilities for the processing of quartz resources.
[0019] 3) The quartz sand purification method provided by the present invention has the advantages of a simple and clear process flow, easy operation and control, and remarkable purification effect. These characteristics make the present technical solution very suitable for large-scale industrial production, and can effectively improve production efficiency and reduce production costs while ensuring product quality.
[0020] Therefore, the technical solution of the present invention has broad application prospects and significant economic value in the field of quartz sand purification. Description of the Drawings
[0021] Figure 1 XRD pattern of the quartz sand raw material in Example 1; it can be seen from the figure that the mineral phase of the quartz sand sample is a pure quartz phase, and almost no associated mineral impurity phase can be seen, indicating that its impurity elements are mainly present in the quartz sand lattice. Detailed Embodiments
[0022] The following further details the content of the present invention in combination with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by those skilled in the art without creative efforts still fall within the protection scope of the present invention.
[0023] Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be obtained through the market or prepared by existing methods.
[0024] The dynamic roasting furnace involved in the following embodiments is a rotary kiln.
[0025] Example 1
[0026] Load quartz sand with a SiO 2 content of 99.9941% into a roasting furnace. Use XRD to analyze that the sample mineral phase is a pure quartz phase without associated mineral impurities, that is, the impurity elements are present in the quartz sand lattice. Introduce H 2 and Cl 2 into the furnace, and their contents are 0.3 and 1.1 times the total molar amount of the impurity elements in the quartz sand respectively. Roast at 1050 °C for 30 min. After collecting and cooling the roasted product, digest the sample according to the requirements of GB∕T 32650-2016 to measure the contents of 13 impurity components, and then calculate that the SiO 2 content of the roasted product is 99.9966%.
[0027] Example 2
[0028] Load quartz sand with a SiO 2 content of 99.9963% into a roasting furnace. Use XRD to analyze that the sample mineral phase is a pure quartz phase without associated mineral impurities, that is, the impurity elements are present in the quartz sand lattice. Introduce CH 4 and Cl 2 into the furnace, and their contents are 1.0 and 0.9 times the total molar amount of the impurity elements in the quartz sand respectively. Roast at 900 °C for 20 min. After collecting and cooling the roasted product, digest the sample according to the requirements of GB∕T 32650-2016 to measure the contents of 13 impurity components, and then calculate that the SiO 2 content of the roasted product is 99.9982%.
[0029] Example 3
[0030] Introduce quartz sand with a SiO 2 content of 99.9952% into a roasting furnace. Use XRD to analyze that the sample mineral phase is a pure quartz phase without associated mineral impurities, that is, the impurity elements are present in the quartz sand lattice. Introduce H 2 and HCl into the furnace at the same time, and their contents are 0.9 and 1.3 times the total molar amount of the impurity elements in the quartz sand respectively. The horizontal inclination angle of the dynamic roasting furnace is 20°, the rotation speed is 5 r / min, and roast at 1200 °C for 15 min. After collecting and cooling the roasted product, digest the sample according to the requirements of GB∕T 32650-2016 to measure the contents of 13 impurity components, and then calculate that the SiO 2 content of the roasted product is 99.9981%.
[0031] Example 4
[0032] Introduce quartz sand with a SiO 2Quartz sand with a content of 99.9944% is introduced into the roasting furnace. The mineral phase of the sample is analyzed by XRD as a pure quartz phase without associated mineral impurities, that is, the impurity elements are present in the quartz sand lattice. CO and HCl are simultaneously introduced into the furnace, and their contents are 1.2 and 1.1 times the total molar amount of the impurity elements in the quartz sand respectively. The horizontal inclination angle of the dynamic roasting furnace is 25°, the rotation speed is 15 r / min, and roasting is carried out at 1100 °C for 5 min. After the roasted product is collected and cooled, the contents of 13 impurity components are measured after digesting the sample according to the requirements of GB∕T 32650-2016, and then the SiO of the roasted product is calculated 2 The content is 99.9962%.
[0033] Example 5
[0034] Introduce SiO 2 Quartz sand with a content of 99.9961% is introduced into the roasting furnace. The mineral phase of the sample is analyzed by XRD as a pure quartz phase without associated mineral impurities, that is, the impurity elements are present in the quartz sand lattice. H 2 and Cl 2 are simultaneously introduced into the furnace, and their contents are 0.8 and 1.1 times the total molar amount of the impurity elements in the quartz sand respectively. The horizontal inclination angle of the dynamic roasting furnace is 5°, the rotation speed is 30 r / min, and roasting is carried out at 1050 °C for 25 min. After the roasted product is collected and cooled, the contents of 13 impurity components are measured after digesting the sample according to the requirements of GB∕T 32650-2016, and then the SiO of the roasted product is calculated 2 The content is 99.9993%.
[0035] Example 6
[0036] Introduce SiO 2 Quartz sand with a content of 99.9941% is loaded into the roasting furnace. The mineral phase of the sample is analyzed by XRD as a pure quartz phase without associated mineral impurities, that is, the impurity elements are present in the quartz sand lattice. H 2 and Cl 2 are simultaneously introduced into the furnace, and their contents are 0.3 and 1.1 times the total molar amount of the impurity elements in the quartz sand respectively. The horizontal inclination angle of the dynamic roasting furnace is 20°, the rotation speed is 30 r / min, and roasting is carried out at 1050 °C for 30 min. After the roasted product is collected and cooled, the contents of 13 impurity components are measured after digesting the sample according to the requirements of GB∕T 32650-2016, and then the SiO of the roasted product is calculated 2 The content is 99.9972%. Compared with Example 1, this example shows that using a dynamic roasting furnace is more conducive to the deep removal of lattice impurities in quartz sand.
[0037] Comparative Example 1
[0038] Compared with Example 1, the only difference is that: H 2The dosage is 0.1 times the total molar amount of impurity elements in quartz sand, and the SiO content of the finally obtained calcined product is 2 99.9949%.
[0039] Comparative Example 2
[0040] Compared with Example 3, the only difference is that the calcination temperature is 750 °C, and the SiO content of the finally obtained calcined product is 2 99.9961%.
[0041] Comparative Example 3
[0042] Compared with Example 4, the only difference is that the calcination time is 3 min, and the SiO content of the finally obtained calcined product is 2 99.9946%.
Claims
1. A high-purity quartz sand enhanced chlorination purification method, characterized in that: The quartz sand raw material containing crystal structure impurities is placed in a roasting furnace, and a gas chlorinating agent and a gas reducing agent are simultaneously introduced into the roasting furnace for roasting to obtain purified quartz sand; The amount of the gaseous chlorinating agent is 0.9 to 1.3 times the total molar amount of impurity elements in the quartz sand; The amount of the gas reducing agent is 0.3 to 1.2 times the total molar amount of impurity elements in the quartz sand; The calcination conditions are: temperature of 900-1200° C. and time of 5-30 min.
2. A high-purity quartz sand enhanced chlorination purification method according to claim 1, characterized in that: The gaseous chlorinating agent includes at least one of hydrogen chloride and chlorine.
3. A high-purity quartz sand enhanced chlorination purification method according to claim 1, characterized in that: The gas reducing agent includes at least one of H2, CO, and CH4.
4. A high-purity quartz sand enhanced chlorination purification method according to claim 1, characterized in that: The roasting furnace is a static roasting furnace or a dynamic roasting furnace.
5. A high-purity quartz sand enhanced chlorination purification method according to claim 4, characterized in that: When the roasting furnace is a dynamic roasting furnace, the horizontal inclination angle of the roasting furnace during the roasting process is 5-25°, and the rotation speed is 3-30 r / min.
Citation Information
Patent Citations
Chloridizing system and chloridizing method for producing high-purity quartz sand
CN104418334A
Purification method of quartz sand
CN113184859A
Equipment and method for purifying quartz sand in high-temperature atmosphere
CN115490237A
Method for preparing quartz from low-grade pegmatite quartz ore
CN118698724A
Purification of silica-based raw material
JP1992050132A
Cited By
Chlorination process for producing high-purity quartz sand
CN121269722A
Method for preparing ultra-pure quartz sand through deep purification
CN121405101A
Method for preparing ultra-high purity quartz sand by deep purification
CN121405101B
Quartz flotation collecting agent, preparation method thereof and flotation method for obtaining different grades of quartz through cascade flotation
CN121423132A
Preparation method of high-purity quartz sand for quartz glass material
CN121627002A